Glass Curtain Wall Technology and Sustainability in Commercial Buildings in Auckland, New Zealand (International Journal of Built Environment and Sustainability, 2020)
Glass curtain wall provides an attractive building envelope, but it is generally regarded as unsustainable because of the high energy needed to maintain thermal comfort. This research explores the advances in the technology of glass cladding and the complex issues associated with judging its sustainability. It assesses the technology and sustainability of glass curtain wall on a sample of thirty commercial buildings in Auckland, New Zealand. Field observations of the glass-clad buildings, coupled with surveys of the building occupants and of glass cladding professionals are used to investigate the cladding characteristics, operational performance, sustainability aspects and future trends. The majority of the sample buildings are low-rise office buildings. The occupants like the aesthetics and indoor environment quality of their glass-clad buildings. However, continuous heating, ventilation and air conditioning are needed in order to maintain thermal comfort within the buildings and this has high energy consumption. The increasing use of unitized systems with double glazing instead of stick-built systems with single glazing improves the sustainability of the cladding through less material wastage and better energy efficiency. Inclusion of photovoltaic modules in the curtain wall also improves energy efficiency but it is currently too expensive for use in New Zealand. Environmental sustainability is also improved when factors such as climate, the orientation of glazed façades, solar control, ventilation and the interior building layout are considered. Any assessment of glass curtain wall sustainability needs to consider the economic and social aspects as well as the environmental aspects such as energy use
Keywords: Glass curtain wall; Stick-built; Unitized; Energy use; Sustainability